PROPSEA, safety evaluation of palbociclib and ribociclib in older patients with breast cancer: A prospective real-world TOG study - ARIKAN, RUKİYE (My University, 2023)
Introduction: In this study, the toxicities and management of palbociclib and ribociclib in older patients (≥65 years) with metastatic breast cancer patients were investigated. Materials and Methods: Among older patients receiving palbociclib and ribociclib, Geriatric 8 (G8) and Groningen Frailty Index were used to evaluate frailty status. Dose modifications, drug withdrawal and other serious adverse events (SAEs) were recorded and analyzed according to baseline patient characteristics. Results: A total of 160 patients from 28 centers in Turkey were included (palbociclib = 76, ribociclib = 84). Forty-three patients were ≥ 75 years of age. The most common cause of first dose modification was neutropenia for both drugs (97% palbociclib, 69% ribociclib). Liver function tests elevation (10%) and renal function impairment (6%) were also causes for ribociclib dose modification. Drug withdrawal rate was 3.9% for palbociclib and 6% for ribociclib. SAEs were seen in 11.8% of those taking palbociclib and 15.5% of those on riboclib. An ECOG performance status of ≥2 and being older than 75 years were associated with dose reductions. Severe neutropenia was more common in patients with non-bone-only metastatic disease, those receiving treatment third-line therapy or higher, coexistance of non-neutropenic hematological side effects (for ribociclib). Neutropenia was less common among patients with obesity. Discussion: Our results show that it can be reasonable to start palbociclib and ribociclib at reduced dose in patients aged ≥75 years and/or with an ECOG performance status ≥2.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Geriatri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Oncology; Geriatrics; Health Sciences; Klinik Tıp (MED); Klinik Tıp; ONKOLOJİ; GERİATRİ ve GERONTOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; ONCOLOGY; GERIATRICS & GERONTOLOGY; Geriatri ve Gerontoloji; Geriatrics and Gerontology; Adverse events; Breast cancer; CDK 4/6 inhibitors; Geriatrics; CDK 4/6 inhibitors; Breast cancer; Adverse events